Pendampingan Implementasi Merdeka Belajar Kampus Merdeka (MBKM) pada Kegiatan Kampus Mengajar - Didik Cahyono; Gyta Krisdiana Cahyaningrum; Muhammad Sukron Fauzi; Naheria Naheria (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The aim of providing assistance for the implementation of independent campus learning in the Class 7 Teaching Campus activities is to facilitate and create a discussion space for students who are interested in taking part in the teaching campus program to develop themselves and contribute to changes in the field of education, provide insight and motivation, and train readiness and equip students regarding the contributions that will be carried out in the campus teaching program. The focus of this article is to analyze the results of assistance in the implementation of independent learning at the independent campus in the Class 7 Teaching Campus activities. The service location is at FKIP, Mulawarman University, targeting students of the Physical Education study program class of 2021. The implementation method used is in stages including observation, interviews, socialization and documentation. The implementation of assistance for the implementation of independent independent campus learning in Class 7 Teaching Campus activities was very helpful in delivering the 15 students who passed and contributed to the Class 7 Teaching Campus activities in 2024 according to their placement at target schools that had been determined in the Teaching Campus program.